Técnica laparoscópica transabdominal preperitoneal comparada con la de lichtenstein en reparación de hernia inguinal en el Hospital Víctor Lazarte Echegaray - Tuesta Barboza, Ramón (2014)
Inguinal hernia is one of the most common disease in general surgery. There are many surgical techniques to repair inguinal hernia. Since the advent of laparoscopic surgery, inguinal hernia repair presents challenges and comparable results with the open technique. Objective: Determine the effectiveness trans-abdominal pre peritoneal laparoscopic technique compared with Lichtenstein technique in inguinal hernia repair at Víctor Lazarte Echegaray hospital. Material and Methods: Observational, analytical, historical cohort study. Review of medical records and call phone or personal interview of patients operated of inguinal hernia for abdominal pre peritoneal laparoscopic technique (36 patients) and Lichtenstein technique (36 patients) at Víctor Lazarte Echegaray hospital during the period January 2008 to December 2012. Results: We don´t found statistically significant difference in inguinal hernia recurrence (2 = 0.00 p>0,05) with 2, 8 % of recurrence for each technique. Conclusion: Trans-abdominal pre peritoneal laparoscopic technique is as effective as Lichtenstein technique to repair inguinal hernia